2020
DOI: 10.1007/s41095-020-0189-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for digital try-on: Challenges and progress

Abstract: Digital try-on systems for e-commerce have the potential to change people's lives and provide notable economic benefits. However, their development is limited by practical constraints, such as accurate sizing of the body and realism of demonstrations. We enumerate three open challenges remaining for a complete and easy-to-use try-on system that recent advances in machine learning make increasingly tractable. For each, we describe the problem, introduce state-of-the-art approaches, and provide future directions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The total statistics are calculated based on the mean, median, and minimum standard values of the number of standard deviations. Figures 15a, 15b, and 15c show the number of daily visitors to the particular website and the conversion rate of the products, which is done [28,29]. Figure 16 shows the amount of seed forecast, which is based on the overall summation of total sales that have been achieved by the particular customer in the product type.…”
Section: Website Usage Analytics Sentiment Positive Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The total statistics are calculated based on the mean, median, and minimum standard values of the number of standard deviations. Figures 15a, 15b, and 15c show the number of daily visitors to the particular website and the conversion rate of the products, which is done [28,29]. Figure 16 shows the amount of seed forecast, which is based on the overall summation of total sales that have been achieved by the particular customer in the product type.…”
Section: Website Usage Analytics Sentiment Positive Feedbackmentioning
confidence: 99%
“…Figure 14 shows the total number of daily visits by the user. This is captured in the data 15 show the number of daily visitors to the particular website and the conversion rate of the products, which are done [28,29]. Figure 16 shows the amount of seed forecast, which is based on the totally real, effective board, and the total sales that have been achieved by the particular customer in the product type.…”
Section: Website Usage Analytics Sentiment Positive Feedbackmentioning
confidence: 99%
“…Virtual try-on provides customers with optimal fit, and it is crucial to understand the fit of garments before the purchase to avoid returns (Hwangbo et al, 2020). Other studies confirmed that the application of this technology as an in-store try-on has the potential to minimize the distance between online and offline shopping (Cordier et al, 2001;Shin and Baytar, 2014;Adikari et al, 2020;Gauri et al, 2021;Liang & Lin, 2021).…”
Section: Virtual Try-onmentioning
confidence: 98%
“…Competition in the fashion industry promotes non-stop apparel overproduction and overconsumption. Moreover, the boom of online sales has increased the volume of online returns, where the wrong sizing and fitting are demonstrated being the main reasons for online customers to return purchased apparel (Yang and Xiong, 2019;Adikari et al, 2020;Gauri et al, 2021;Liang & Lin, 2021). This problem is being addressed through the development of virtual and augmented reality (VR & AR) apps and digital innovations, such as robot mannequins, systems-based algorithms, 3D technology.…”
Section: Thesis Statementmentioning
confidence: 99%
“…However, in backlight or insufficient light conditions, smartphones cannot capture clear images. Low-light images will show varying degrees of degradation, such as low brightness and contrast, unexpected noise, which seriously affect the visual effect [1]. In order to improve the quality of low-light images, we can enhance it from the perspective of supplementing light, increasing sensitivity and extending exposure.…”
Section: Introductionmentioning
confidence: 99%